2008
DOI: 10.1530/eje-08-0107
|View full text |Cite
|
Sign up to set email alerts
|

Serum osteoprotegerin concentrations are decreased in women with the polycystic ovary syndrome

Abstract: Objective: Osteoprotegerin (OPG), an inhibitor of osteoclastic bone resorption, has a variety of functions including anti-inflammatory effects and a possible cardiovascular protective role. Both low-grade chronic inflammation and cardiovascular risk are increased in women with the polycystic ovary syndrome (PCOS). We aimed to study serum OPG concentrations in PCOS patients. Design: Case-control study including 40 PCOS patients matched with 40 non-hyperandrogenic women for age and body mass index. Methods: Basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 62 publications
1
13
1
1
Order By: Relevance
“…Low serum OPG levels were previously reported by Escobar-Morreale et al (24) but in contrast to our findings, the authors failed to detect any association between OPG and glucose metabolism parameters in PCOS women of similar age. It should be pointed out, however, that in our study the HOMA was used, primarily expressing hepatic insulin resistance, whereas in Escobar-Morreale's research, the insulin sensitivity index during oral glucose tolerance test according to Matsuda & DeFronzo was chosen, which rather provides information on whole-body (hepatic and peripheral, in particular muscle) insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Low serum OPG levels were previously reported by Escobar-Morreale et al (24) but in contrast to our findings, the authors failed to detect any association between OPG and glucose metabolism parameters in PCOS women of similar age. It should be pointed out, however, that in our study the HOMA was used, primarily expressing hepatic insulin resistance, whereas in Escobar-Morreale's research, the insulin sensitivity index during oral glucose tolerance test according to Matsuda & DeFronzo was chosen, which rather provides information on whole-body (hepatic and peripheral, in particular muscle) insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, it was shown that serum OPG concentrations are decreased in PCOS and related to hyperandrogenemia (24). However, the relationship of OPG to endothelial injury, one of the initiating events of atherosclerosis, has not been yet described in PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Preserved BMD and the hyperinflammatory state in PCOS could be associated with increased OPG levels. Recent studies, however, reported decreased [53,54] or unchanged [55] OPG levels in PCOS patients versus controls. OPG levels were positively associated with vitamin D, BMD and testosterone, but also with I-CTP, a marker of bone resorption [55].…”
Section: Bone Turnover Markers In Pcosmentioning
confidence: 99%
“…OPG levels were positively associated with vitamin D, BMD and testosterone, but also with I-CTP, a marker of bone resorption [55]. In contrast, Pepene and Escobar-Morreale reported inverse associations between OPG, Ferriman-Gallwey score and free testosterone levels in PCOS, but did not measure BMD [54,53]. Intervention studies in hypogonad men [45] and in transsexual women [56] documented significantly increased BMD [45] and increased OPG/RANKL levels [56] after testosterone treatment, thus supporting the positive association between testosterone levels, OPG and BMD.…”
Section: Bone Turnover Markers In Pcosmentioning
confidence: 99%
“…Osteoprotegerin (OPG) has both anti-inflammatory and antiapoptotic effects, particularly at the level of endothelial cells, where it exerts a protective role in the development of atherosclerotic plaque and plaque rupture (Scatena and Giachelli, 2002;Schoppert et al, 2002;Kiechl et al, 2007;Kim et al, 2005, as cited in Repaci et al, 2011). Reduced levels of OPG have been observed in obesity and in the presence of insulin resistance (Ugur-Altun et al, 2005;Holecki et al, 2007, as cited in Repaci et al, 2011, as well as in PCOS (Escobar-Morreale et al, 2008), where they were related to the androgen excess (Escobar-Morreale et al, 2008). Interestingly, we have demonstrated very recently that circulating OPG was negatively and significantly correlated with FMD and, moreover, that PCOS women in the upper OPG quartile group (> 2.65 pmol/l) presented significantly altered endothelial function compared to all the rest.…”
Section: Classic and Non-classic Markers Of Low-grade Inflammation Inmentioning
confidence: 99%